Portable and visual assays for the detection of SARS‐CoV‐2. Issue 1 (31st January 2022) - Zhang, Yufan; Ding, Dan
Abstract: Corona virus disease 2019 (COVID‐19) is a serious contagious disease that arises from severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). The disease is transmitted primarily through droplets transmission, which does not exclude the possibility of transmission through aerosols and digestive tract and other means. The majority of COVID‐19 cases present as common and mild, while a few cases progress rapidly to the severe and critical stage, making it more difficult to save the disease. Current laboratory diagnostic approaches for COVID‐19 are on the basis of pathogenic tests for viral nucleic acids, serological tests by specific antibody detection, and general tests. For now, Real‐time quantitative PCR (qRT‐PCR) is the gold standard for the detection of COVID‐19, but the method is complicated and may have false‐negative results. Therefore, in order to diagnose and prevention COVID‐19 more effectively, it is needful to develop highly sensitive diagnostic methods with portable instruments and visualized results. This mini‐review provides an overview of the current portable and visual assays of detection of COVID‐19, in order to achieve early effective and more accurate diagnosis of COVID‐19. Abstract : Corona virus disease 2019 (COVID‐19) is a serious contagious disease that arise from severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). This mini‐review provides an overview of the current portable and visual assays of detection of COVID‐19, in order to achieve early effective and more accurate diagnosis of COVID‐19.